Left‐sided and duplicate inferior vena cava: A case series and review. Issue 8 (10th May 2012) - Ang, Wee Choen; Doyle, Terry; Stringer, Mark D.
<x xml:space="preserve">Abstract</x> Left‐sided and duplicate inferior vena cava (IVC) are two major anatomical variants within the spectrum of IVC malformations, both of which are developmental abnormalities of the supracardinal veins. Four clinical cases are described to highlight the computed tomographic appearances of these vascular malformations and provide novel data on venous dimensions. A systematic review of the recent literature (2000–2011) was conducted focusing on the anatomy, demographics, and associated pathology (congenital and acquired) of isolated left‐sided and duplicate IVC. A total of 73 relevant articles were retrieved, consisting of case reports and small case series. The prevalence of left‐sided IVC is about 0.1–0.4% and that for duplicate IVC about 0.3–0.4%; both anomalies show a slight male preponderance. In each condition, there are documented variations in the course and tributaries of the IVC. The clinical importance of these anomalies lies in three principal areas: the potential for misdiagnosis on imaging; technical difficulties during retroperitoneal surgery (particularly abdominal aortic aneurysm repair and live donor nephrectomy); and their significance in relation to the etiology and management of venous thromboembolism. Clin. Anat. 26:990–1001, 2013. © 2012 Wiley Periodicals, Inc.